2023
DOI: 10.3389/fcimb.2023.1206111
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic herpes simplex viruses for the treatment of glioma and targeting glioblastoma stem-like cells

Abstract: Glioblastoma (GBM) is one of the most lethal cancers, having a poor prognosis and a median survival of only about 15 months with standard treatment (surgery, radiation, and chemotherapy), which has not been significantly extended in decades. GBM demonstrates remarkable cellular heterogeneity, with glioblastoma stem-like cells (GSCs) at the apex. GSCs are a subpopulation of GBM cells that possess the ability to self-renew, differentiate, initiate tumor formation, and manipulate the tumor microenvironment (TME).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 168 publications
0
8
0
Order By: Relevance
“…The immune response, responsible for clearing OVs and hindering their replication, is a major reason for the effectiveness of oncolytic virotherapy. Combining OVs with immunosuppressants, such as anti-PD1 antibodies, has shown promise in clinical trials (137). Achieving a balance between immune response and clearance through the use of immunosuppressants and multi-dose OVs delivery requires further investigation.…”
Section: Future Directionsmentioning
confidence: 99%
“…The immune response, responsible for clearing OVs and hindering their replication, is a major reason for the effectiveness of oncolytic virotherapy. Combining OVs with immunosuppressants, such as anti-PD1 antibodies, has shown promise in clinical trials (137). Achieving a balance between immune response and clearance through the use of immunosuppressants and multi-dose OVs delivery requires further investigation.…”
Section: Future Directionsmentioning
confidence: 99%
“…Compared to the normal cellular microenvironment, TME is characterized by hypoxia, low pH, high interstitial pressure, high vascular permeability, and an inflammatory response; TME is closely related to GC resistance to TMZ, and long‐term use of TMZ may exacerbate immunosuppression in glioma TME. 81 , 82 Angiogenic factors are particularly active in glioma TME, including transforming growth factor beta, hypoxia‐inducible factor, cyclooxygenase‐2, fibroblast growth factor, and helper T cell 2 cytokines. 83 , 84 Inhibition of the production of angiogenic factors, especially in glioma TME, and blocking the blood supply to the tumor are targets of action of many antiangiogenic agents.…”
Section: Advances In Chemotherapy For Gliomamentioning
confidence: 99%
“…When its deleted, HSV-1 cannot complete lytic infection in neurons and thus does not cause encephalitis. Upon inactivation of ICP6, encoding a large subunit of ribonucleotide reductase (RR), the virus is able to replicate only in actively proliferating cells (e.g., tumor cells) with high levels of host RR [39]. In Phase 1 of a clinical trial, G207 showed a strong effect against pediatric high-grade gliomas.…”
Section: Herpes Simplex Virusmentioning
confidence: 99%
“…In preclinical studies, the only oncolytic virus approved for use in patients with glioblastoma, G47∆, was evaluated in combination with etoposide [18,39]. Etoposide is a semi-synthetic derivative of podophyllotoxin.…”
Section: Virotherapy In Combination With Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation